1995
DOI: 10.1056/nejm199511023331806
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Intervention to Prevent the Readmission of Elderly Patients with Congestive Heart Failure

Abstract: A nurse-directed, multidisciplinary intervention can improve quality of life and reduce hospital use and medical costs for elderly patients with congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
1,315
5
45

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,019 publications
(1,412 citation statements)
references
References 23 publications
31
1,315
5
45
Order By: Relevance
“…Cardiac cachexia, characterized by muscle wasting, inflammation, insulin resistance, weight loss, and anorexia, is an independent risk factor for mortality in patients with HF 8. In contrast, nutritional intervention may improve clinical outcomes with less hospitalization and medical cost, especially in older patients with HF 26. Consequently, a clinically significant nutritional index is indicated for risk stratification and clinical management of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac cachexia, characterized by muscle wasting, inflammation, insulin resistance, weight loss, and anorexia, is an independent risk factor for mortality in patients with HF 8. In contrast, nutritional intervention may improve clinical outcomes with less hospitalization and medical cost, especially in older patients with HF 26. Consequently, a clinically significant nutritional index is indicated for risk stratification and clinical management of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Seven randomized trials in the United States whose enrollees averaged from 65 to 76 years identified or recruited patients as inpatients, sometimes with the requirement that they be at least 70 years old. [22][23][24][25] Current or recent inpatients and their families may be more likely to agree to participate, perhaps because they feel more at risk of the condition's complications and more open to approaches to reduce that risk.…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies show that comprehensive discharge planning, including medication counseling and review along with increased communication and follow-up, can help reduce readmissions. 9 In addition, the use of implantable cardiac devices combined with optimal medical therapy has successfully reduced hospitalization rates for patients with HF. 10 Many prior studies on readmission rates have been limited to single-center experiences over a period of several years.…”
Section: Introductionmentioning
confidence: 99%